Further look at correlation between ASTM G65 rubber wheel abrasion and pin-on-disc wear tests for data conversion. (September 2013) - Fu, L; Li, L; Li, D Y
Abstract : It is desirable that wear testing results obtained using different techniques can be mutually converted. In this study, wear rates of two groups of materials, i.e. cast iron and steel, were evaluated using the ASTM G65 dry sand rubber wheel abrasion and pin-on-disc wear testers respectively. The conversion between results obtained using the two different methods was investigated. It was shown that the two sets of wear data can be mutually converted, following a linear relation. The slope and position of the line that fits the data are, however, affected by Young's modulus of the materials and the applied load. Such effects are attributed to the fact that the wear rate of the materials measured using the G65 method was influenced by not only hardness but also elastic modulus, while for the pin-on-disc tests, the wear rate was more dominated by hardness of the target materials especially under larger applied loads. Relevant mechanisms are discussed with a further look at the Archard's wear equation.